2015
DOI: 10.1039/c5nr04856g
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-free synthesis of Ag–In–Se alloy nanocrystals with visible emissions

Abstract: As promising heavy metal-free emitting materials, Ag-In-Se nanocrystals (NCs) are conventionally synthesized using organic phosphine agents and exhibit near-infrared emissions. In this work, we demonstrate a rapid phosphine-free approach for synthesizing Ag-In-Se alloy NCs with the emissions tunable to the visible region on the basis of the phosphine-free dissolution of Se powder. At room temperature, Se powder is reduced by dodecanethiol and dissolved in oleylamine to produce a Se precursor. The resultant Se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 67 publications
2
47
0
Order By: Relevance
“…It can also be considered that orthorhombic Ag 2 Se nucleus after insertion of In 3+ ions lead to formation of tetrahedral AISe NCs however, this phase transforms immediately in to orthorhombic at higher reaction temperature (typically above 200 ο C). In recent past, Yao et al have proposed similar reaction pathway as well as phase transformation above190 °C for AISe NCs when synthesized at variable temperature. Similar trend was obtained for samples prepared using oleyl amine instead of oleic acid (Figure (II, a, b, c).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…It can also be considered that orthorhombic Ag 2 Se nucleus after insertion of In 3+ ions lead to formation of tetrahedral AISe NCs however, this phase transforms immediately in to orthorhombic at higher reaction temperature (typically above 200 ο C). In recent past, Yao et al have proposed similar reaction pathway as well as phase transformation above190 °C for AISe NCs when synthesized at variable temperature. Similar trend was obtained for samples prepared using oleyl amine instead of oleic acid (Figure (II, a, b, c).…”
Section: Resultsmentioning
confidence: 85%
“…The peaks obtained at 2θ 33.4, 34.7, 37.0, 40.0, 44.9 ο due to (112), (121), (013), (031) and (032) crystal planes confirming the presence of Ag 2 Se NCs in both of these samples. However, presence of orthorhombic AISe NCs cannot be ruled out since there is an intense peak at 2θ 25.6 ο along with low intensity peaks at 42 ο and 42.8 ο resulted from (202), (040) and (320) crystal planes of an orthorhombic crystal structure . It is thus concluded that the reactions carried out for 3 h and 4 h resulted in formation of Ag 2 Se along with AISe NCs.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This broad emission band (full width at half maxima >100 nm) is an indication of the formation of alloyed QDs. 30 The peak maximum is gradually red shied due to the faster growth of QDs at higher temperatures. The reaction temperature dependent PL spectra of AZ4 and AZ6 QDs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…29 The intensity of the lower wavelength band gradually increases with an increase in the reaction temperature which indicates higher incorporation of Zn 2+ and In 3+ into the vacant sites of Ag 2 Se. 14,28,30 At elevated temperatures, these two bands merge into a broad intense emission band. This broad emission band (full width at half maxima >100 nm) is an indication of the formation of alloyed QDs.…”
Section: Resultsmentioning
confidence: 99%